Contribution to the knowledge of Stenochironomus Kieffer (Diptera, Chironomidae) from Brazil: seven new species and description of females and immatures of some previously known species - Dantas, Galileu P. S.; Hamada, Neusa; Mendes, Humberto F. (Zootaxa, 2016)
Twenty two species of Stenochironomus Kieffer are known from Brazil, 19 of which occur in the Amazon region. In order to increase knowledge of the taxonomy of this genus in the Amazon region, collections were carried out in streams located in Presidente Figueiredo, Manaus and Itacoatiara municipalities, Amazonas State. Leaves and wood mined by Stenochironomus larvae were collected and transported to the laboratory where they were kept until adult emergence. Seven new species were found, one of which is described in the immature stages and as adults of both sexes (S. amazonicus sp. n.), one as immatures and adult male (S. liviae sp. n.), four as male and pupa (S. bare sp. n., S. figueiredoensis sp. n., S. gracilis sp. nov. and S. manauara sp. n.) and one only as male (S. suzanae sp. n.). Additionally, the female, pupa and larva of S. impendens Borkent, pupa and larva of S. jubatus Borkent, female and pupa of S. zonarius Borkent and female of S. palliaculeatus Borkent were described.